Development and validation of a clinical decision-making aid for screening bowel symptoms in community pharmacies - Sriram, Deepa; McManus, Alexandra; Emmerton, Lynne; Parsons, Richard; Jiwa, Moyez (Wiley-Blackwell Publishing Ltd., 2014)
Rationale, aims and objectives: Bowel symptoms are common, and community pharmacies are an ideal setting for health advice about these symptoms. The aim of this study was to develop and validate a questionnaire for use with adults presenting to community pharmacies with lower bowel symptoms. The purpose of the questionnaire was to stratify people into those requiring medical follow-up for symptoms and those with self-limiting symptoms. Method: A self-administered questionnaire, named the Jodi Lee test (JLT), was developed in three stages – review of the literature, questionnaire design and statistical validation – against a validated screening tool, the patient consultation questionnaire (PCQ), to assess the sensitivity and specificity of JLT. The questionnaire was developed to be simple, easy for all pharmacy staff to use and require no score calculation. Its application was designed to facilitate referral from pharmacy assistants to pharmacists and from pharmacists to medical practitioners. Results: The questionnaire comprises eight questions. It has a Flesh–Kincaid reading score of 79.5. By considering different score thresholds on the PCQ, a receiver operator characteristic (ROC) curve was calculated to assess the effectiveness of the JLT. From a sample of 118 subjects, the area under the ROC curve was 0.94. At a threshold score of 30 on the PCQ, the sensitivity was 100%. The specificity was 65%. Conclusion: The JLT has high sensitivity for identifying patients with symptoms of serious bowel disease. It is also likely to identify patients who have symptoms of relatively benign disease who would benefit from medical advice.